2022
DOI: 10.1101/2022.09.27.509727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ubiquitin conjugase Rad6 mediates ribosome pausing during oxidative stress

Abstract: Oxidative stress causes K63-linked ubiquitination of ribosomes by the E2 ubiquitin conjugase, Rad6. How Rad6-mediated ubiquitination of ribosomes affects global translation, however, is unclear. We therefore performed Ribo-seq and Disome-seq in Saccharomyces cerevisiae, and found that oxidative stress caused ribosome pausing at specific amino acid motifs, and this also led to ribosome collisions. However, these redox pausing signatures were lost in the absence of Rad6 but did not depend on the ribosome-associa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…First, we showed that exposure to either H 2 O 2 or 4-NQO show decreased translation rate compared to untreated rates in wild-type cells (Fig 5A), with a 10-fold decrease in H 2 O 2 , a 4-fold decrease in the lower concentration of 4-NQO, and a more than 20-fold decrease in the higher concentration of 4-NQO. In alignment with our previous findings (Meydan et al ., 2023), H 2 O 2 -induced suppression of active translation was dependent only on Rad6 expression (Fig 5A). Under low concentration of 4-NQO (In 1 μg/mL), deletion of RAD6 had no significant effect on translation suppression, corroborating our findings that the RTU is not induced by 4-NOQ.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…First, we showed that exposure to either H 2 O 2 or 4-NQO show decreased translation rate compared to untreated rates in wild-type cells (Fig 5A), with a 10-fold decrease in H 2 O 2 , a 4-fold decrease in the lower concentration of 4-NQO, and a more than 20-fold decrease in the higher concentration of 4-NQO. In alignment with our previous findings (Meydan et al ., 2023), H 2 O 2 -induced suppression of active translation was dependent only on Rad6 expression (Fig 5A). Under low concentration of 4-NQO (In 1 μg/mL), deletion of RAD6 had no significant effect on translation suppression, corroborating our findings that the RTU is not induced by 4-NOQ.…”
Section: Resultssupporting
confidence: 94%
“…We sought to determine whether the RQC is induced in a stress-specific manner by testing the ability of the RQC to clear stalled ribosomes using an established reporter system (Matsuo et al ., 2017). The inducible dual-luciferase reporter contains either a No-Stall control or 6xCGA polyarginine sequence inserted between Renilla luciferase (Rluc) and Firefly (Fluc) encoding regions (Fig 4C) (Meydan et al ., 2023). Stretches of positively charged peptide sequences, especially those encoded by rare codons like CGA, are known to induce ribosome stalling (Barros et al , 2021; Chen et al , 2024; Matsuo et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tripeptide pause scores were computed as described previously (Meydan et al 2023). Briefly, this involved dividing the 80S reads per million (rpm) of a three-amino acid motif by the average rpm in the surrounding region (±50 nt around each motif).…”
Section: Methodsmentioning
confidence: 99%